Doing qualitative research differently : a psychosocial approach - Hollway, Wendy; Jefferson, Tony. (London : SAGE, 2013)
"Wendy Hollway and Tony Jefferson have updated their ground-breaking book for students and researchers looking to do qualitative research d ifferently. The new edition critically reviews many of the assumptions, claims and methods of qualitative research and also acts as a 'how to' guide to the method the authors call the Free Association Narrative In terview. In the new edition, the authors situate their arguments firml y within a tradition of psychosocial research and show how their method has developed over the last decade. The book follows this approach thr ough the phases of empirical research practice. At each stage they use examples from their own research and end with an extended case study wh ich demonstrates the value of their method in producing a psychosocial research subject; that is, one with socially-imbued depth, complexity a nd biographical uniqueness."--Publisher's website.
The Need to Do Research Differently -- Researching the Fear of Crime -- Producing Data with Defended Subjects -- Analyzing Data with Defend ed Subjects -- The Ethics of Researching Psychosocial Subjects -- Biogr aphy, Demography and Generalizability -- A Psychosocial Case Study -- O riginal Afterword -- New Developments since 2000.
Previous ed.: 2000.
Includes bibliographical references (p. [168]-176) and index.
Keywords: Social sciences -- Research; Qualitative research. -- Research